Frequency of reoperations in patients with Marfan syndrome - Geisbüsch, Sarah; Bischoff, Moritz (The annals of thoracic surgery, 2012)
Background We undertook a retrospective study of the pattern of reoperations in surgical patients with Marfan disease. Methods Between 1985 and 2008, 83 Marfan patients (60 males, 23 females) underwent 155 aortic operations in our institution. Twenty-eight patients had acute dissection (22 type A, 6 type B), and two had aortic rupture. Mean age at initial operation was 32 ± 13 years. Operations included valve-sparing or Bentall aortic root repair, and ascending aorta, arch, descending thoracic, thoracoabdominal aorta, and infrarenal aortic replacement. Sixty-one patients whose initial operation was elective (Group I) were compared with 22 patients with initial emergency surgery (Group II). Results Overall, 81/83 patients ultimately underwent root/ascending repair: 64% initially and 36% at reoperation. Operative mortality in Group I was 1.6% for both initial operations and reoperations vs 9.0% and 0% in Group II. Significant differences between Group I and Group II patients included: total reoperations (1 vs 3, p = 0.05); arch operations (0 vs 1, p = 0.003); descending thoracic aortic operations (0 vs 0.5, p = 0.003); and total aortic segments replaced (1.6 ± 1.0 vs 2.4 ± 1.1, p = 0.001). Survival at 5 and 10 years did not differ between Group I and II patients (87% and 71% vs 82% and 56%, p = 0.19). Conclusions lthough reoperation occurs in about half of surgical Marfan patients, reoperative mortality is low. Patients with initial elective procedures fare better than those with initial emergency surgery: they have fewer subsequent operations, fewer aortic segments replaced, and trend toward improved survival. Elective root replacement should be seriously considered in any Marfan patient with significant root dilatation.